THEORETICAL AND PRACTICAL ASPECTS REGARDING THE INDEPENDENCE OF THE ROMANIAN OMBUDSMAN - Oana ŞARAMET (Bulletin of Transilvania University of Braşov Series VII: Social Sciences • Law • Vol. 16(65) No. 1 – 2023, 2023)
The Romanian Ombudsman (the Romanian People's Advocate) is an autonomous and independent public authority, as provided for by the law on the organization and functioning of this public institution, which is not part of any of the three powers in the state - legislative, executive and judicial. The decision of the constitutional legislator not to include this public institution in any of the three classic powers was determined, in our opinion, by the desire, but also the need, to configure an impartial institution that would exercise its constitutional and legal role with complete objectivity. In this context, through this paper, we propose to analyse, through specific research methods, such as the comparative, sociological, teleological method, if the way of appointing and, respectively, of revoking the head of this institution is one that does not affect this role, risking politicizing the institution of the Ombudsman.
Keywords: ombudsman; appointment; dismissal from office; politicisation; objectivity; independent